2014
DOI: 10.1039/c4cc05936k
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum phosphide: a new highly efficient catalyst for the electrochemical hydrogen evolution reaction

Abstract: Molybdenum phosphide was adopted as a new electrocatalyst for the hydrogen evolution reaction for the first time, exhibiting an excellent electrocatalytic activity with a small Tafel slope of 60 mV dec(-1), which is amongst the most active, acid-stable, earth abundant HER electrocatalysts reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
131
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 225 publications
(137 citation statements)
references
References 22 publications
5
131
1
Order By: Relevance
“…2. We can see that the FeMoP-0.10 catalyst is large aggregated clusters composed of small nanoparticles, similar to the morphology and microstructure of pure MoP [11]. The element distribution of Fe, Mo and P was revealed by the SEM-EDX elemental mapping, demonstrating that these elements are well dispersed without remarkable sintered aggregations, as shown in Fig.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…2. We can see that the FeMoP-0.10 catalyst is large aggregated clusters composed of small nanoparticles, similar to the morphology and microstructure of pure MoP [11]. The element distribution of Fe, Mo and P was revealed by the SEM-EDX elemental mapping, demonstrating that these elements are well dispersed without remarkable sintered aggregations, as shown in Fig.…”
Section: Resultsmentioning
confidence: 64%
“…Remarkably, the FeMoP-0.10 catalyst exhibits the smallest Tafel slope, demonstrating the best HER activity among all the MoP-based catalysts. Compared to the pure MoP catalyst (60 mV dec -1 ) [11], the FeMoP-0.12 and FeMoP-0.14 even show larger Tafel slopes of 69 and 72 mV dec -1 , indicating worse HER activity. It can be concluded that only a suitable content of Fe can ensure the great enhancement of the final HER activity.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations